2021
DOI: 10.1039/d0nr06747d
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the cellular toxicity of benzo[a]pyrene from the view of nanoclusters: size- and nanoplastic adsorption-dependent bioavailability

Abstract: Nanoplastics serve as carriers for Bap nanoclusters and alter the toxicity difference of Bap nanoclusters formed in aqueous solution with tunable sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The study of apoptotic markers in lung cells exposed to NPs and plasticizers verified the disturbance of the mitochondrial membrane potential [ 31 , 33 ]. It was also observed that the alteration ATP production and deregulation of the energy production mechanism [ 33 , 35 ] contributed towards cell damage [ 17 , 20 , 37 ]. Consequently, cell death has been reported [ 17 , 49 ] particularly for long exposure periods [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of apoptotic markers in lung cells exposed to NPs and plasticizers verified the disturbance of the mitochondrial membrane potential [ 31 , 33 ]. It was also observed that the alteration ATP production and deregulation of the energy production mechanism [ 33 , 35 ] contributed towards cell damage [ 17 , 20 , 37 ]. Consequently, cell death has been reported [ 17 , 49 ] particularly for long exposure periods [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For organic compounds such as benzo(a)pyrene (BaP), which its presence in the air is related to the attachment to the airborne solid particulates [ 60 ], its adsorption can affect physicochemical properties, and consequently, the cellular response to NPs [ 61 , 62 ]. According to the articles included in this review [ 20 , 33 , 34 ], there is evidence of alterations in cell viability with exposure to phthalates and BaP nanoclusters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sorption of PAHs to plastic particles is dependent on complicated interactions between the compounds' exposed functional groups. For example, it has recently been demonstrated that, once in the water, PAHs such as benzo[a]pyrene (BaP) can take the form of self-aggregated nanoclusters, rather than free dissolved forms [96]. Insoluble BaP nanoclusters may stably bind to NPs (for example, 190 nm PS-NPs) and enter the cell via NP clathrin-and phagocytosis-mediated endocytosis.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs) and Polychlorinated ...mentioning
confidence: 99%